Improving simulated consumption context with virtual Reality: A focus on participant experience. (June 2022) - Yang, Qian; Nijman, Marit; Flintham, Martin; Tennent, Paul; Hidrio, Claire; Ford, Rebecca
Highlights: An immersive environment was created using innovative 360° video and object tracking with 3D modelling. Audio, time and people presence in 360° video increased perceived realism. Questionnaire responses using a tracked pen and scale on the table is perceived as intuitive. VR is shown to generate higher participant engagement than Evoked context with pictures and sound. A training VR session is recommend to remove the novelty effect on product evaluation. Abstract: Context can have a significant impact on liking, emotional response and product choice, and Virtual Reality (VR) is a promising tool to evoke realistic consumption contexts in a controlled testing environment. This study compared an innovative approach – combining a 360° video and a 3D model with object tracking to an Evoked context using pictures and sound recordings to simulate a realistic consumption environment for beer (i.e. bar). This study explored consumer experience of the innovative VR design and measured their engagement with it compared to an Evoked scenario. Additionally, participants' emotional response and liking between the two contexts and the effect of including a VR training session prior to data collection were also explored. In total, 27 beer consumers participated in this study. The novel VR method that was developed for this study consisted of 360° video footage recorded in a bar with sound, which was projected around a virtual table model with an integrated questionnaire, using a pen and beer bottles attached to tracking devices. The Evoked context consisted of a picture slideshow and sound recording to simulate the exact same bar context. An interview was conducted after the VR training session to explore consumer experience of the VR design. Participant engagement was then measured after participants completed both the VR and Evoked sessions respectively. The results showed that the VR session had clear advantages in terms of participant engagement compared to the Evoked session. Audio, the time spent in VR, and realistically simulated presence of other people were identified as key elements that improved realism and immersion of the VR context, whilst low image quality and technical problems had the opposite effect. The first exposure to VR was shown to have high novelty and further impact on the emotional response to beer, which highlighted the importance of having a training/dummy session to reduce VR novelty and associated effect.